1998
DOI: 10.1017/s1431927600023394
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Pin Point Failure Analysis Using Fib Combined Analytical Tem

Abstract: Recently, we developed the dedicated FIB system(FB-2000A) for the TEM specimen preparation. The system has ion optics with the maximum ion beam current density of 15 A/cm2 and the minimum ion probe size of l0nm. In the system, the side entry type specimen stage originally designed for high resolution TEM was employed, and the drift rate of the stage during FIB milling is less than lnm/min. The FIB-TEM compatible specimen holder has been developed it made milling of specimen in FIB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…With the rapid maturation of FIB instruments has come an equally rapid diversification of applications. In addition to TEM specimen preparation, FIB milling techniques have also been effective in producing specimens for subsequent analysis by scanning electron microscopy~SEM!, secondary ion mass spectrometry~SIMS!, scanning transmission electron microscopy~STEM!, AUGER electron spectroscopy~AES!, and atomic force microscopy~AFM; Mackenzie et al, 1993Mackenzie et al, , 1994Young et al, 1993a;Huffman et al, 1994;Ishitani et al, 1995;Kamino et al, 1998;Prenitzer et al, 1998;Stevie et al, 1999Stevie et al, , 2001Vartuli et al, 1999!. It should be noted that the fundamental concepts of ion-solid interactions presented in this work are equally applicable to any such potential application.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…With the rapid maturation of FIB instruments has come an equally rapid diversification of applications. In addition to TEM specimen preparation, FIB milling techniques have also been effective in producing specimens for subsequent analysis by scanning electron microscopy~SEM!, secondary ion mass spectrometry~SIMS!, scanning transmission electron microscopy~STEM!, AUGER electron spectroscopy~AES!, and atomic force microscopy~AFM; Mackenzie et al, 1993Mackenzie et al, , 1994Young et al, 1993a;Huffman et al, 1994;Ishitani et al, 1995;Kamino et al, 1998;Prenitzer et al, 1998;Stevie et al, 1999Stevie et al, , 2001Vartuli et al, 1999!. It should be noted that the fundamental concepts of ion-solid interactions presented in this work are equally applicable to any such potential application.…”
Section: Introductionmentioning
confidence: 79%
“…TEM specimen preparation have been described in the literature, this article will refer extensively to the FIB lift-out~FIB LO! method~Kirk et al, 1989; Young et al, 1990;Basile et al, 1992;Sanborn and Myers, 1992;Yater and Thompson, 1992;Overwijk et al, 1993Overwijk et al, , 1998Ishitani et al, 1994;Stevie et al, 1995Stevie et al, , 1998aHerlinger et al, 1996;Giannuzzi et al, 1997;Phaneuf et al, 1997;Sheng et al, 1997;Kamino et al, 1998;Young et al, 1998;Zhou and Zanoya, 1999;Langford and Petford-Long, 2001!.…”
Section: Introductionmentioning
confidence: 99%
“…In the experiment, the Hitachi FB-2000A FIB system equipped with the FIB-TEM-compatible side entry specimen holder and Hitachi HF-2000 cold field emission analytical TEM equipped with secondary electron microscopy (SEM) and scanning transmission electron microscopy (STEM) capabilities were used (Kamino et al, 1998). The FIB-TEM-compatible specimen holder employed in the system was designed to enable a specimen to be totally inverted so that SEM observation of both cross-sectional surfaces was possible.…”
Section: Methodsmentioning
confidence: 99%
“…For example, results of our recent experiments revealed that structurally and elementally complicated composite materials such as magneto-optical (MO) disks could be easily and properly thinned for high-resolution electron microscopy (HREM) and EDX analysis (Yaguchi et al, 1999). In this study, we discuss the method to prepare a crosssectional thin specimen (Kamino et al, 1998) from a specific precipitate in a steel using a combination of a dedicated FIB system and an intermediate voltage TEM. Application of the method to the characterization of a precipitate in a steel is also described.…”
Section: Introductionmentioning
confidence: 99%